Ex vivo efficacy of BCMA‐bispecific antibody TNB‐383B in relapsed/refractory multiple myeloma. Issue 1 (1st August 2020) - Foureau, David M.; Bhutani, Manisha; Robinson, Myra; Guo, Fei; Pham, Duy; Buelow, Ben; Steuerwald, Nury; Rigby, Katherine; Tjaden, Elise; Leonidas, Marina; Paul, Barry A.; Atrash, Shebli; et al.
Abstract: TNB‐383B is a fully human BCMA‐targeting T‐cell engaging bispecific monoclonal antibody (T‐BsAb). We assessed ex vivo efficacy of this drug to mediate killing of bone marrow mononuclear cells (BMMCs) freshly isolated from 10 patients with relapsed multiple myeloma (MM). BMMC were treated ex vivo with TNB‐383B at doses ranging from 0.001‐1 μg. Plasma cell (PC) lysis, viability, BCMA expression, CTL distribution, and degranulation were assessed by flow cytometry. Cytokine response to TNB‐383B was quantified by multiplex protein assay. Dose‐dependent PC lysis was triggered in all cases by TNB‐383B at doses as low as 0.001 μg ( P = .0102). Primary MM cells varied in BCMA expression. High BCMA + PC count correlated with increased PC lysis ( P = .005) and significant CTL degranulation specific to TNB‐383B treatment ( P = .0153 at 1 μg). High E:T ratio in bone marrow specimens led to lower viable and higher apoptotic PC compared with low E:T ratio ( P < .001). Three cytokines were significantly modulated by TNB‐383B: IL‐2/TNFα increased by ∼4 ± 3.5‐fold average ( P < .005 at 1 μg) and IP10 increased by ∼50 ± 15‐fold ( P < .001 at 1 μg). We conclude that TNB‐383B triggers primary PC lysis and CTL degranulation in a dose‐dependent fashion ex vivo with no T cell expansion and mild increase of CRS‐associated cytokines.